The Relationship between Academic Procrastination and Information-Seeking Behavior among Students in the Library and Information Science Program at Universitas Negeri Padang - Regina Putri; Nurizzati (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Academic procrastination is a major behavioral challenge that may adversely affect students’ academic performance and their capacity to seek, evaluate, and use scholarly information effectively. This study aims to examine the relationship between academic procrastination and information-seeking behavior among undergraduate students in the Library and Information Science Program at Universitas Negeri Padang. A quantitative correlational design was employed, involving 61 students selected through proportionate stratified random sampling. Data were collected using a structured questionnaire developed from the indicators of Temporal Motivation Theory for academic procrastination and Ellis’s Information-Seeking Behavior Model for information-seeking behavior. The data were analyzed using descriptive statistics, Pearson product–moment correlation, and the coefficient of determination. The findings reveal a significant negative relationship between academic procrastination and information-seeking behavior (r = −.692, p < .001), indicating that higher levels of procrastination are associated with less effective information-seeking behavior. Academic procrastination accounted for 47.9% of the variance in information-seeking behavior. The study concludes that reducing academic procrastination may enhance students’ ability to seek information systematically and effectively. These findings contribute to the literature on self-regulated learning and information behavior and provide practical implications for universities in designing interventions that strengthen students’ time management, self-regulation, and information literacy competencies.